Anatomical study of the ideal cortical bone trajectory in the lumbar spine. Issue 2 (15th January 2021) - Zhao, Yong-Hui; Ma, Yu-Long; Wang, Long; Liang, Jin-Long; Luo, Hao-Tian; Xu, Yong-Qing; Lu, Sheng
Abstract: Background: To explore the ideal trajectory of lumbar cortical bone trajectory screws and provide the optimal placement scheme in clinical applications. Methods: Lumbar computed tomography (CT) data of 40 patients in our hospital were selected, and the cortical vertebral bone contour model was reconstructed in three dimensions (3D). Depending on the different regions of the screw through the entrance and exit of the pedicle, 9 trajectories were obtained through combinational design: T-Aa, T-Ab, T-Ac, T-Ba, T-Bb, T-Bc, T-Ca, T-Cb, and T-Cc. Cortical bone trajectory (CBT) screws with appropriate diameters were selected to simulate screw placement and measure the parameters corresponding to each trajectory (screw path diameter, screw trajectory length, cephalad angle, and lateral angle), and then determine the optimal screw according to the screw parameters and screw safety. Then, 23 patients in our hospital were selected, and the navigation template was designed based on the ideal trajectory before operation, CBT screws were placed during the operation to further verify the safety and feasibility of the ideal trajectory. Results: T-Bc and T-Bb are the ideal screw trajectories for L1–L2 and L3–L5, respectively. The screw placement point is located at the intersection of the inner 1/3 vertical line of the superior facet joint and the bottom 1/3 horizontal line of the outer crest of the vertebral lamina (i.e., 2–4 mm inward at the bottom 1/3 of the outer crest of the vertebral lamina). CBT screws were successfully placed based on the ideal screw trajectory in clinical practice. During the operation or the follow-up period, there were no adverse events. Conclusion: CBT screw placement based on the ideal screw trajectory is a safe and reliable method for achieving effective fixation and satisfactory postoperative effects.